Profiling the Quality and Quantity of Naturally Induced Antibody Responses Against Pfs230 and Pfs48/45 Among Non-Febrile Children Living in Southern Ghana: A Longitudinal Study - Broni, Fermin K.; Acquah, Festus K.; Obiri-Yeboah, Dorcas; Obboh, Evans K.; Sarpong, Esther; Amoah, Linda E. (Frontiers in Cellular and Infection Microbiology, 2021)
A clear understanding of the properties of naturally induced antibody responses against transmission-blocking vaccine candidates can accelerate the understanding of the development of transmission-blocking immunity. This study characterized the naturally induced IgG responses against two leading transmission-blocking vaccine antigens, Pfs230 and Pfs48/45 in non-febrile children living in Simiw, Ghana. Consecutive sampling was used to recruit 84 non-febrile children aged from 6 to 12 years old into the 6-month (November 2017 until May 2018) longitudinal study. Venous blood (1 ml) was collected once every two months and used to determine haemoglobin levels, P. falciparum prevalence using microscopy and polymerase chain reaction, the levels and relative avidity of IgG responses against Pfs230 and Pfs48/45 using indirect ELISA. IgG levels against Pfs230 and Pfs48/45 decreased from the start (November) to the middle (January) and end (March) of the dry season respectively, then they began to increase. Participants, especially older children (10 – 12 years old) with active infections generally had lower antibody levels against both antigens. The relative avidities of IgG against both antigens followed the trend of IgG levels until the middle of the dry season, after which the relative avidities of both antigens correlated inversely with the antibody levels. In conclusion, although IgG antibody levels against both Pfs48/45 and Pfs230 began to increase by the early rainy season, they were inversely correlated to their respective relative avidities.